ANALISIS YURIDIS KETENTUAN PASAL 10 UNDANG-UNDANG NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI (STUDI KASUS TINDAK PIDANA OLEH LGBT DI MUKA UMUM) - Gunawan, Tri Agus; Bhakti, Indira Swasti Gama (Universitas Wahid Hasyim Semarang, 2020)
Abstract The discussion about the problem of pornography seems to be endless. The ease of accessing cyberspace is one of the causes of pornography being difficult to control. The emergence of minority groups such as LGBT (lesbian, gay, bisexual, and transgender) raises its own problems in the community. Some human rights activists consider LGBT a right for those who are not used to being banned and even the State must protect it. In terms of human values, it is clear that LGBT actors must indeed be protected from discrimination. But if their actions have touched the public or public domain, that is no longer a reason to be protected by the State and even the State must appear in regulating it. When the LGBT action was publicly displayed, Law Number 44 Year 2008 Regarding Pornography, could not directly touch it. This is influenced by two factors, namely regulation factors and also implementation factors. The source of this regulation must be immediately addressed so that its implementation is not ambiguous. Displaying pornographic acts by LGBT in public has been very worrying and can damage the mentalities of young people, especially children. Whereas in the sense of pornography as regulated in Article 1 number 1, the acts of the LGBT offender have entered the qualifications of pornography, namely in the case of